THE CONCEPT AND FUNCTIONS OF EUPHEMISMS IN LANGUAGE - N. A. Baratova; Х. Х. Turabayeva (Web of Journals Publishing, 2025)
Euphemisms play an important role in social communication, helping to reduce emotional stress and create comfortable conditions for interaction in society.
Keywords: Euphemisms, softening, veiling, direct expression, sensitive topics.